Biomarker pattern of ARIA-E participants in phase 3 randomized clinical trials with bapineuzumab. (6th March 2018) - Liu, Enchi; Wang, Dai; Sperling, Reisa; Salloway, Stephen; Fox, Nick C.; Blennow, Kaj; Scheltens, Philip; Schmidt, Mark E.; Streffer, Johannes; Novak, Gerald; Einstein, Steve; Booth, Kevin; et al.
Abstract : Objective: To evaluate whether amyloid-related imaging abnormalities with edema/effusion (ARIA-E) observed in bapineuzumab clinical trials was associated with specific biomarker patterns. Methods: Bapineuzumab, an anti-β-amyloid monoclonal antibody, was evaluated in patients with mild to moderate Alzheimer disease. Amyloid PET imaging, CSF biomarkers, or volumetric MRI (vMRI) were assessed. Results: A total of 1, 512 participants underwent one or more biomarker assessments; 154 developed incident ARIA-E. No differences were observed at baseline between ARIA-E and non-ARIA-E participants in brain amyloid burden by PET, the majority of vMRI measures, or CSF biomarkers, with the exception of lower baseline CSF Aβ42 in APOE ε4 noncarrier ARIA-E vs non-ARIA-E groups (bapineuzumab non-ARIA-E p = 0.027; placebo non-ARIA-E p = 0.012). At week 71, bapineuzumab-treated participants with ARIA-E vs non-ARIA-E showed greater reduction in brain amyloid PET, greater reductions in CSF phosphorylated tau (p-tau) (all comparisons p < 0.01), and total tau (t-tau) (all comparisons p < 0.025), and greater hippocampal volume reduction and ventricular enlargement (all p < 0.05). Greater reduction in CSF Aβ40 concentrations was observed for ARIA-E versus both non-ARIA-E groups (bapineuzumab/placebo non-ARIA-E p = 0.015/0.049). No group differences were observed at week 71 for changes in whole brain volume or CSF Aβ42 . Conclusions: Baseline biomarkers largely do not predict risk for developing ARIA-E. ARIA-E was associated with significant longitudinal changes in several biomarkers, with larger reductions in amyloid PET and CSF p-tau and t-tau concentrations, and paradoxically greater hippocampal volume reduction and ventricular enlargement, suggesting that ARIA-E in bapineuzumab-treated cases may be related to increased Aβ efflux from the brain and affecting downstream pathogenic processes.